(untitled) (African Journal of Biomedical Research, 2021)
In Nigeria, the impact of household food insecurity on nutritional status especially nutrient intake adequacy of under-5 children has not been fully explored. This study aimed to evaluate household food security and nutritional status of under-5 children in Ibadan, southwestern Nigeria. A multi-stage sampling approach was used to select households with mothers who have at least one under-5 child. Information was elicited through an interviewer administered questionnaire and a multi-pass 24hr dietary recall method. The results presented in this study reflect low food security status of households with more than half of households being food insecure (63%) and experiencing some form of hunger within the study period. A low socioeconomic status was observed in most of the sampled households which may have reduced purchasing power for food expenditure. While anthropometric indices did not reveal a major problem with the children’s nutritional status, the quality of their diet as deduced from nutrient adequacy analysis revealed high micronutrient inadequacy in Vitamin A (82%), Vitamin C (80%), Folate (44%), Potassium (91%), Zinc (91%), and Iron (74%). This study shows that even though households may be above the severe hunger status, the quality of the diet may be insufficient to provide needed nutrition for health security of household members especially under-5 children.